2007
DOI: 10.1002/anie.200701744
|View full text |Cite
|
Sign up to set email alerts
|

Two SiSi Double Bonds Connected by a Phenylene Bridge

Abstract: Electronic communication between two SiSi double bonds is enabled by a phenylene linkage and expressed in a large red shift of the longest‐wavelength UV/Vis absorptions of deep red tetrasiladiene 1 compared to yellow phenyldisilene 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 45 publications
3
56
0
2
Order By: Relevance
“…Calculations for 12 have demonstrated that the LUMO level is lowered [-1.552 (5a) and -2.108 (12) eV], thus keeping the HOMO levels nearly constant [-5.141 (5a) and -5.137 (12) eV], in agreement with the orbital shapes for 5a and the previously mentioned electrochemical experimental results. The significant 3n-2p p conjugation are also found in the HOMO-2 and HOMO-3 of 12.…”
Section: Theoretical Studies Of P-conjugated Phosphasilenessupporting
confidence: 84%
See 3 more Smart Citations
“…Calculations for 12 have demonstrated that the LUMO level is lowered [-1.552 (5a) and -2.108 (12) eV], thus keeping the HOMO levels nearly constant [-5.141 (5a) and -5.137 (12) eV], in agreement with the orbital shapes for 5a and the previously mentioned electrochemical experimental results. The significant 3n-2p p conjugation are also found in the HOMO-2 and HOMO-3 of 12.…”
Section: Theoretical Studies Of P-conjugated Phosphasilenessupporting
confidence: 84%
“…The calculated wavelengths of 364 (5a) and 456 (12) nm are comparable to the observed values. The absorption at 364 nm of 5a is assignable to the mixed version of the HOMO!LUMO (p-p*) and HOMO-1!LUMO ((n + p of Eind benzene)-p*) transitions with almost equal weighting.…”
Section: Theoretical Studies Of P-conjugated Phosphasilenessupporting
confidence: 83%
See 2 more Smart Citations
“…Especially Scheschkewitz and Tamao should be mentioned in this context, as they independently reported the synthesis of various π conjugated systems containing Si Si units. 11,12 Their disilenes consist of extended π conjugated systems with bridged and terminal phenylene or phenyl groups, exhibiting particularly interesting photochemical properties. Wishing to combine the remarkable developments in the eld of extended π electron systems containing heavier main group elements and d π electron systems, lead us to investigate the chemistry of a new type of d π electron systems with a π electron spacer of heavier main group elements.…”
Section: Introductionmentioning
confidence: 99%